On Quantum Methods for Machine Learning Problems Part II: Quantum Classification Algorithms - Farid Ablayev; Marat Ablayev; Joshua Zhexue Huang; Kamil Khadiev; Nailya Salikhova; Dingming Wu (Big Data Mining and Analytics)
This is a review of quantum methods for machine learning problems that consists of two parts. The first part, "quantum tools", presented some of the fundamentals and introduced several quantum tools based on known quantum search algorithms. This second part of the review presents several classification problems in machine learning that can be accelerated with quantum subroutines. We have chosen supervised learning tasks as typical classification problems to illustrate the use of quantum methods for classification.